Pengaruh Rehabilitasi Medik Terhadap Tingkat Stress Pasien Karsinoma Mammae Pasca Operasi Di RS Kanker Dharmais - Ichwan, Hafidz Nur; Riyadi, Slamet; Sahir, Endang (Nexus Kedokteran Klinik, 2013)
Background: Carcinoma mammae is a cancer of thoracal region that most commonly found and suffered by women in Indonesia. Cancer patients may experience morbidity and psychiatric disorder. With rehabilitation, physical and psychological disorders which were caused by cancer could be reduced. This study aims to determine effects of medical rehabilitation towards stress level of post-surgical mammary carcinoma patients. Methods: This research is observational analytic study with cross-sectional approach. Subjects were patients who came to the clinic of Oncology and Medical Rehabilitation Installation of National Cancer Centre Dharmais. Research subjects were taken by purposive sampling technique. The research data were obtained through interviews using questionnaires. The collected data were statistically analyzed with Chi Square test using SPSS 17 software for Windows program. Results: From the research results, there is total 60 patients. Medium-category stress patients were 53 people, 25 people (47.2%) had never undergone medical rehabilitation, and 28 people (52.8%) had undergone medical rehabilitation. Severe-category stress patients were 7 people, 5 people (71.4%) had never undergone medical rehabilitation and 2 people (28.6%) had undergone medical rehabilitation. The results of calculations acquired a significance level of XÂ²count is 0.228 > significance level of p = 0.05. Conclusions: Based on the result of statistical analysis, it can be concluded that there is no significant effects of medical rehabilitation towards stress level of post-surgical mammary carcinoma patients. Keywords: Carcinoma Mammae â Medical Rehabilitation â Stress Level